2021
DOI: 10.1002/jgh3.12663
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of lenvatinib in nonviral unresectable hepatocellular carcinoma

Abstract: Aim: To investigate the therapeutic effect of lenvatinib (LEN) in liver disease etiology, especially nonviral hepatocellular carcinoma (HCC). Methods and Results: Sixty-seven patients with unresectable advanced HCC (u-HCC) treated with LEN and consisting of 26 hepatitis C virus (HCV), 19 hepatitis B virus (HBV), 11 alcohol, and 11 nonalcoholic steatohepatitis (NASH) cases were retrospectively recruited. Univariate and multivariate Cox proportional hazard models were used to determine predictive factors for sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 48 publications
(89 reference statements)
2
9
0
Order By: Relevance
“…Previous clinical studies on LEN have reported a similar age and male sex ratio. 12,32 The prevalence of MAFLD was 48.6% in the present study, which was similar to its prevalence in other studies that investigated the impact of MAFLD on HCC (45.4%-68.4%). 33,34 In the AEs associated with LEN, the prevalence of hypertension, proteinuria, fatigue, and appetite loss above grade 3 was 11.2%, 10.6%, 7.8%, and 5.0%, respectively.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous clinical studies on LEN have reported a similar age and male sex ratio. 12,32 The prevalence of MAFLD was 48.6% in the present study, which was similar to its prevalence in other studies that investigated the impact of MAFLD on HCC (45.4%-68.4%). 33,34 In the AEs associated with LEN, the prevalence of hypertension, proteinuria, fatigue, and appetite loss above grade 3 was 11.2%, 10.6%, 7.8%, and 5.0%, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…11 The impact of NASH on the treatment efficacy of LEN remains controversial. 7,12,13 Recently, a new definition for fatty liver disease, metabolic dysfunction-associated fatty liver disease (MAFLD), was proposed by an international expert panel. 14,15 MAFLD is characterized by the inclusion criteria of metabolic abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Another retrospective study from Japan found better outcomes for patients with alcohol- or NASH-related HCC ( n =22) than for patients with HBV- or HCV-related HCC ( n =45) in terms of objective response rate (59.1% vs. 46.7%), median progression-free survival (13.7 vs. 6.6 months, p <0.01), and median overall survival (“not reached” vs. 15.9 months, p <0.01). 105 In an international multicenter retrospective study of 1,232 patients with advanced HCC, those who also had NASH showed significantly higher overall and progression-free survival than patients with HCV or HBV infection or other etiologies after first-line treatment with lenvatinib. 76 A retrospective study in the USA showed 12-month progression-free survival rates of 64.9% for 233 patients with total advanced HCC after first-line lenvatinib therapy, compared to 43.0% for the subset of 32 patients who also had NASH.…”
Section: Systemic Therapymentioning
confidence: 99%
“… 102 , 103 , 108 However, these studies did not perform subgroup analyses based on NAFLD or NASH status. Recently, a meta-analysis 105 of the randomized controlled trials CheckMate 459, 109 IMbrave150, 110 and KEYNOTE-240 111 found that ICI treatment was effective against virus-related HCC but ineffective against HCC unrelated to viral infection. Consistently, three studies found significantly better overall survival after ICI therapy among patients with HCC unrelated to NAFLD than among those with NAFLD-related HCC.…”
Section: Systemic Therapymentioning
confidence: 99%
“…showed that in HCC patients treated with lenvatinib, the objective response rate (ORR) was higher in the nonviral group than in the viral group, although the difference was not significant. While the progression-free survival (PFS) and overall survival (OS) was significantly longer in the nonviral group than the viral group, suggesting that nonviral status might serve as a biomarker for lenvatinib treatment ( 12 ). The authors held that fibroblast growth factor 19 - fibroblast growth factor receptor 4 (FGF19-FGFR4) pathway, which was target of lenvatinib, were involved in the tumorigenesis of non-alcoholic steatohepatitis- and alcohol-associated HCC and consequently, these HCCs responded better to lenvatinib.…”
Section: Clinical Factorsmentioning
confidence: 99%